Comparison of root and shoot traits of different wheat species and wild wheat relatives: Does feature of shoot biomass have positive and significant relationships with grain yield and root traits? - Akman, Hayati; Akgün, Necdet; Tamkoç, Ahmet (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2017)
This study targeted to investigate some root and shoot traits and theirrelationship in 47 different genotypes such as cultivars, lines, landraces, ancient wheat species and wild wheat relatives belonging to 14 different species at long tubes of PVC under field weather conditions. It was found significant differences between genotypes in terms of root and shoot traits (P<0.01). The investigated raits varied among the genotypes, ranging from 0.97 to 6.88 g for root biomass, 0.07 to 0.34 for root to shoot ratio, 5.9 to 25.0% for root to total biomass ratio, 4.3 to 34.7 for tiller number and 7.5 to 52.6 g for shoot biomass. Ancient wheat species such as Triticum monococcum (Kelycras), T. turgidum, T. spelta, a landrace  (Vanlı), and cultivars (Daws High PPO, ARS Amber and AK 702) had large root  biomass among the genotypes. Therefore, these genotypes could be helpful for improving genotypes with large root system in breeding programs. The study also showed that shoot biomass had significant and positive relationships with root biomass (0.572**), root length (0.441**) and crown root number (0.245**) as well as grain yield (0.911**). Accordingly, feature of shoot biomass might be used as selection criteria in breeding program to improve genotypes with superior rootsystem and high grain yield.